Horacio, Odas II, 14: apuntes para un comentario - López Muñoz, Manuel (1991)
In this paper, the author tries a methodological approach to the problem of stylistic commentaries on latin poetical texts. In this sence, the main point of the method is the use of a deductive criterium, not an inductive one. Considering that any analysis aiming at objetivity should be built on the basis of empiric data, either statistical or of any other kind, the author works out a frequential distribution of alliterations and metrical irregularities occuring along Horace's Ode II, 14 to try and determine zones of accumulation of those phaenomena: the target of this delimitation is to be able to divide a text in parts -the first step of a commentary- without the perjudices which we are used to see in the inductive-traditional methodology.
Keywords: Horacio Flaco, Quinto; Odas; Crítica literaria